Effect of Nitrogen in Combination with Different Levels of Sulfur on Wheat Growth and Yield - Dawar, Khadim; Khan, Aftab Ahmed; Jahangir, Mohammad Mofizur Rahman; Mian, Ishaq Ahmad; Khan, Bushra; Ahmad, Bashir; Fahad, Shah; Moustafa, Mahmoud; Al-Shehri, Mohammed; Mubashir, Muhammad; Datta, Rahul; Danish, Subhan (ACS omega, 2023)
As macronutrients, management of nitrogen (N) and sulfur (S) is prime in importance when wheat is cultivated. Both have a significant impact on the improvement of growth and yield attributes. In addition, S and N also play an imperative role in the enhancement of seed protein contents. However, the need of the time is the selection of their optimum application rate for the achievement of maximum wheat productivity. That is why the current study was planned to examine the impact of variable application rates of S and N on wheat. There are 12 treatments, i.e., control (no nitrogen (0N) + no sulfur (0S)), 40 kg/ha N (40N + 0S), 80 kg/ha N (80N + 0S), 120 kg/ha N (120N + 0S), 30 kg/ha sulfur (30S), 40N + 30S, 80N + 30S, 120N + 30S, 60 kg/ha sulfur (60S), 40N + 60S, 80N + 60S, and 120N + 60S, applied in three replications. The results showed that plant height, grains/spike, spike/m2, and 1000 grain weight were significantly improved by the addition of 120N + 60S. A significant enhancement of grain N contents, N uptake, and protein contents of wheat validated the efficient role of 120N + 60S over 0N and 0S. In conclusion, 120N + 60S is a better treatment for the achievement of maximum wheat yield. More investigations under variable soil textures and climatic conditions are suggested under different climates to declare 120N + 60S as the best amendment for wheat growth and yield improvement.